KEMAMPUAN PREDIKSI TERHADAP PENDAPATAN DAN ARUS KAS OPERASIONAL LANCAR UNTUK ARUS KAS OPERASIONAL MASA DEPAN - Aliamin, Aliamin (Universitas Muhammadiyah Aceh, 2008)
The aim of this research is to investigate ability prediction of earnings and current operating cash flows to future operating cash flows, the profit report use are firms reporting positive profit and firms reporting negative profit. There are several prior study indicates a strengthening relationship between earnings and future operating cash flows for both firms profit reporting and losses reporting, while relationship between current and future operating cash flows are neither increasing nor decreasing. The result of research indicates that both earnings and cash flows have ability to predict future operating cash flow for positive profit reporting. On the other hand, negative profit reporting, earnings are not significant to predict future operating cash flows while current operating cash flows still have ability to predict future operating cash flows. Key words: earnings, current operating cash flows, future operating cash flows, positive profit reporting, negative profit reporting DAFTAR PUSTAKA Ali, Ashiq. 1994. “The Incremental Information Content of Earnings, Working Capital from Operations and Cash Flows”. Journal of Accountimg Research. Vol. 32, No. 1, pp. 61—73. Barth, Mary E, Donald P. Cram dan Karen K. Nelson. 2001. “Accruals and the Prediction of Future Cash Flows”. The Accounting Review. Vol. 76; pp. 27—58. Bowen, Robert M., David Burgstahler, dan Lane A. Daley. 1986. “Evidence on The Relationship Between Earnings and Various Measures of Cash Flows”. The Accounting Review. (LXI) No. 4. pp 713—725. Cheng, C.S.A., Chao-Shin Liu, dan Thomas F.S. 1996. “Earnings Permanence and the Incremental Information Content of Cash Flows from Operations”. Journal of Accounting Research. Vol. 34, No.1, Spring, 173—181. Dechow, P.M., S.P. Kothari dan R.L. Watts. 1998. “The Relation Between Earnings and Cash Flows”. Journal of Accounting and Economics 25. pp. 133—168. DeFond, Mark dan Mingyi Hung. 2001. An Empirical Analysis of Analysts’ Cash Flow Forecast. http://papers.ssrn.com/sol3/-papers.cfm?abstract_id=265773 Doupnik, T.S., dan F.B. Salter. 1995. “External Environment, Culture, and Accounting Practice: a Preliminary Test of a General Model of International Accounting Development”. The International Journal of Accounting. (30). Pp. 189—207. FASB. 1987. Statement of Financial Accounting Concepts (SFAC) No. 1. Finger, Catherine A. 1994. “The Ability of Earnings to Predict Future Earnings and Cash Flow”. The Journal Accounting Research. Vol. 32, No.2. Autumn. Pp. 210—223. Fridson, Martin S. (1995). Financial Statement Analysis. 2nded. New York : John Wiley and Sons, Inc. Gunawan dan Bandi,.2000. Analisis Kandungan Informasi Laporan Arus Kas, Simposium Nasional Akuntansi III, 697-718 Hendriksen, Eldon S. dan Michael F, Van Breda (1992). Accounting Theory. Fifth Edition Boston : Richard D. Irwin, Inc. Hodgson, A., Peta S., dan Clarke. 2000. “Earnings, Cashflows, and Returns: Functional Relations and the Impact of Firm Size”. Accounting and Finance. 40. pp. 51—73. Ikatan Akuntan Indonesia (2002). Standard Akuntansi Keuangan. Jakarta : Penerbit Salemba Empat. Kieso, Donald E dan Jerry J Weygandt (1998). IntermediaAccounting. Ninth Edition. New York : John & Sons, Inc Kim, Myung-Sun dan William Kross. 2002. The Ability of Earnings to Predict Future Operating Cash Flows Has Been Increasing - Not Decreasing.http://papers.ssrn.com/sol3/Delivery.cfm/SSRN_ID303283_code0203 16500.pdf?abstractid=303283&mirid=1 Kusuma, Poppy Dian Indira. 2003. “Nilai Tambah Kandungan Informasi Laba dan Arus Kas Operasi”. SNA VI, h. 304—315. Ndubizu, G.A. 1992. “Accounting Disclosure Methods and Economic Development: Criterion for Globalizing Capital Markets”. The International Journal of Accounting (27). pp. 151—163. Parawiyati dan Zaki Baridwan. 1998. “Kemampuan Laba dan Arus Kas dalam Memprediksi Laba dan Arus Kas Perusahaan Go Publik di Indonesia”. Jurnal Riset Akuntansi Indonesia. Vol. 1 No. 1, h.1-11. Scroeder, Richard G. dan Myrtle Clark (1998). Accounting Theory-Text and Reading. 6th Edition. Canada : John Willey & Sons, Inc. Supriyadi. 1999. “The Predictive Ability of Earnings Versus Cash Flow Data to Predict Future Cash Flows: a Firm-Specific Analysis”. Gadjah Mada International Journal of Business. Vol. 1, September, h. 113—132. Syafriadi, Hepi. 2000. “Kemampuan Earnings dan Arus Kas dalam Memprediksi Earnings dan Arus Kas Masa Depan: Studi di Bursa Efek Jakarta”. Jurnal Bisnis dan Akuntansi. Vol. 2, No. 1, April, h. 76—88. Wallace, Wanda A. (1997). Financial Accounting. 3rd ed. Cincinati : South Western Publishing. Watson, Jodi dan Peter Wells. 2005. The Association Between Various Earnings and Cash Flow Measures of Firm Performance and Stock Returns: Some Australian Evidence. http://papers.ssrn.com/sol3/papers.cfm?abstract_id=815365. Wilson, P.G. (1986).” The Alternative Information Content of Accrual and Cash Flow: Combined Evidence at The Earnings Anouncement Annual Reports Release Date”. The Accounting research. Vol.24, Supplement, pp.165-200.